Robotic arm gripper using force sensor for crop picking mechanism - Ahmad Radzi, Syafeeza; Abdul Hamid, Norihan; Eng, Man Ling; Lee, Guan Wei; Thai, Hui Jia; Amsan, Azureen Naja (Penerbit Universiti Teknikal Malaysia Melaka, 2022)
A dynamic gripper with qualities that resemble the human hand as closely as possible is sought after in the field of robotics. The idea of a robotic arm has been used invarious cutting-edge technology fields, including agriculture,to assist people or farmers in carrying out regular tasks, such as gathering fruit, etc.The robot arm's end effector is one of the essential parts of the robot that we can configure based on their tasks, such as a spraying adaptor for fertilization function or a gripper for the picking mechanism. Since fruits have a delicate and fragile surfaces, it is vital to have a gripper with a smooth contact surface that can apply the right amount of force to pick the fruits without causing any bruising that can degrade the crop's quality. Hence, this paper proposes a robotic arm gripper design for the crop-picking mechanism using a force sensor as the main component of the Arduino Uno embedded system. There liability result for the chili obtained is around 95% showing that this design is promising for designing an adaptive robotic arm gripper.